Ethical Considerations of Social Networking for Counsellors - Bratt, William Edgar Vernon (Canadian Journal of Counselling and Psychotherapy, 2010)
The use of online social networking websites has increased among Canadians in recent years. There are many professional and ethical implications for counsellors who use these sites (Boyd, 2007). Although they offer advantages to counsellors, their use can also raise issues around ethical conduct. Because the counselling literature has not yet addressed these issues, this article draws on literature in other disciplines. A variety of issues are discussed using multidisciplinary references. The author concludes that online social networks are valuable tools for connecting with friends and loved ones, but that competent practitioners should be aware of the ethical concerns inherent to their use.